Superalloys for Industry Applications - Cevik, Sinem (IntechOpen, 2018)
In recent years, superalloys have been widespread usage in aerospace gas turbine engine parts. The main reason of it is that these materials have high yield, ultimate tensile strength, and very good corrosion/oxidation resistance, and they combine these good properties with an excellent creep resistance at elevated temperatures. In spite of their outstanding properties, superalloys can lose their mechanical strength because of wear, tear, and crack formation when they are exposed to high-service temperatures and heavy working conditions. Moreover, corrosion is another important issue for superalloys because the materials of gas turbine engine parts are exposed to harsh engine environments, which consist of many pollutants and hot gases. Therefore, special attention must be given to the corrosion behavior of superalloys. This book provides information on the interaction between the microstructure of alloys and their mechanical properties and also the position of superalloys in the manufacturing industry. Topics cover the minimization of the formation of microsegregation and detrimental phases in the GTA welding of superalloys, oxidation kinetics of nickel-based superalloys used in the manufacture of rings for aircraft engines, a review of the work done over the last two decades to understand the hot corrosion behavior of superalloys used in advanced coal-based power plants, ultrasonic-assisted machining of Inconel 718, dry high-speed turning of Ti-6Al-4V titanium alloy, and laser welding in dentistry. The book "Superalloys for Industry Applications" consists of contributions by scientists and engineers who are experienced in the production, design, and analysis of materials from all around the world. We hope that this book will be an irreplaceable source of study for manufacturing, degradation mechanisms, and reliability of superalloys.